2012
DOI: 10.4315/0362-028x.jfp-11-175
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Prevalence and Distribution of Microbial Contamination To Evaluate Water Management in the Fresh Produce Processing Industry

Abstract: This study provided insight into the degree of microbial contamination in the processing chain of prepacked (bagged) lettuce in two Belgian fresh-cut produce processing companies. The pathogens Salmonella and Listeria monocytogenes were not detected. Total psychrotrophic aerobic bacterial counts (TPACs) in water samples, fresh produce, and environmental samples suggested that the TPAC is not a good indicator of overall quality and best manufacturing practices during production and processing. Because of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 50 publications
2
63
1
Order By: Relevance
“…However, washing of produce is a potential pathway for spreading contamination among crops (17), and the risk of crosscontamination is not removed by using large quantities of water (18). Chlorine is much more effective for inactivation of bacterial pathogens in wash water than for removal of these pathogens from fresh produce (11,19).…”
mentioning
confidence: 99%
“…However, washing of produce is a potential pathway for spreading contamination among crops (17), and the risk of crosscontamination is not removed by using large quantities of water (18). Chlorine is much more effective for inactivation of bacterial pathogens in wash water than for removal of these pathogens from fresh produce (11,19).…”
mentioning
confidence: 99%
“…Moreover, across the whole chain workers use water for hand washing, and it can be also applied as an ingredient in processing. Studies have demonstrated and discussed that inadequacies in water control can cause food safety problems in fresh produce (e.g., Holvoet, Jacxsens, Sampers, & Uyttendaele, 2012;Tyrrel et al, 2006). Water control with structured sampling for measuring the contamination risks in relation to the water source (or previous use) and intended use of the water is critical (Steele, Mahdi, & Odumeru, 2005).…”
Section: Preventive Control Activitiesmentioning
confidence: 99%
“…This is valid even when potable water is used, because water quality can deteriorate at all stages through improper storage or cross-contamination (Gerba & Choi, 2006;Gerba, Choi, Sapers, Solomon, & Matthews, 2009). Moreover, sampling information is of high importance for selecting the most effective water treatment technologies (EHEDG, 2007;Holvoet et al, 2012;Pachepsky et al, 2011). Sophisticated water control (advanced level) is typified by water control based on statistically underpinned sampling, and treatment that is tailored and tested for efficacy in the company-specific circumstances.…”
Section: Preventive Control Activitiesmentioning
confidence: 99%
See 2 more Smart Citations